Pengaruh Iklan Digital Vindes.store di Instagram Terhadap Keputusan Pembelian(Survei pada followers Instagram @vindes.store) - Fathan Ananta Hirzi; Oktaviana Purnamasari (Jurnal Ilmu Sosial dan Humaniora, 2026)
Utilizing digital media in advertising has become increasingly important for companies offering products or services, as digital advertising enables brands to reach consumers efficiently and target audiences more precisely. One brand implementing this strategy is Vindes.Store. This study aims to examine Vindes.Store’s digital advertising on Instagram, identify purchasing decisions of followers of the Instagram account @vindes.store, and measure the influence of digital advertising on purchasing decisions. Digital advertising is measured through several dimensions in variable X, including Targeting, Interactivity, Measurement and Analytics, Personalization, Cost Effectiveness, Ad Engagement, and Reach and Frequency. Meanwhile, the purchasing decision variable (Y) is measured using the dimensions of Problem Recognition, Information Search, Evaluation of Alternatives, and Purchase Decision. This research uses a quantitative approach by distributing questionnaires to 67 respondents who are followers of @vindes.store and have made purchasing decisions. The sampling technique used is simple random sampling, and the data analysis method applied is simple linear regression. The results show that the t-value is 6.93, higher than the t-table value of 1.997. Therefore, H0 is rejected and H1 is accepted, indicating that digital advertising significantly influences purchasing decisions. The correlation coefficient (R) is 0.652, indicating a strong relationship, while the R Square value is 42.5%.